Gambaran Tingkat Kepuasan Pasien Terhadap Kualitas Pelayanan Obatdi Apotek Kinan Farma Mojosongo Periode November-Desember Tahun 2021 - Destiyani; Nisa, Nisa Amallia; Zaila M.A, Tiara; Agus Santoso, Aris Prio (SEKOLAH TINGGI ILMU FARMASI YAYASAN PHARMASI SEMARANG, 2022)
Pharmaceutical service is a form of professionalism in the health sector which is the responsibility of a health professional, especially pharmacists. A pharmacy is a pharmaceutical service facility where the pharmacy is one of the places for a pharmacist to practice pharmacy. Rapid developments have occurred in pharmacies where there is a new pharmacy paradigm, namely from drug oriented (drug service) to patient oriented (patient service) which refers to pharmaceutical care (pharmaceutical care). The benefits of this study are expected to determine the level of patient satisfaction with service quality and can provide health information to patients in order to improve the quality of drug services at the Kinan Farma Pharmacy. This research is an observational study, where the data is taken using a questionnaire based on the inclusion criteria that have been set. The results showed that the picture of Kinan Farma's pharmacy satisfaction was highest in the dimension of reliability (reliability) with a percentage of 92.3%. Based on the average dimension of satisfaction that was processed, the results obtained a percentage of 87% which indicates a very satisfied category.